2020
DOI: 10.1002/jclp.23071
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, educational, and alternative interventions for reducing fear of childbirth in pregnant women: A systematic review

Abstract: Objective This review aims to identify non‐medical interventions that may reduce the fear of childbirth, directly or indirectly (through its factors). Methods This review followed the PRISMA guidance and a rigorous protocol that was registered in PROSPERO. Searches were done in ProQuest, the International Clinical Trials Registry Platform, and Google Scholar. All RCTs published in the last 5 years, in English or Spanish, regarding women with a low‐risk pregnancy and without mental disorders were included. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 61 publications
0
30
2
Order By: Relevance
“… 34 Identification of severe FOC early in pregnancy will allow healthcare professionals to provide appropriate interventions to support and guide pregnant women and nurture their psychological health throughout pregnancy. Several systematic reviews and meta-analyses revealed that interventions including prenatal education and counseling can reduce women’s FOC; 35–37 thereby reducing the risk for future negative consequences to both psychological and obstetric health.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Identification of severe FOC early in pregnancy will allow healthcare professionals to provide appropriate interventions to support and guide pregnant women and nurture their psychological health throughout pregnancy. Several systematic reviews and meta-analyses revealed that interventions including prenatal education and counseling can reduce women’s FOC; 35–37 thereby reducing the risk for future negative consequences to both psychological and obstetric health.…”
Section: Discussionmentioning
confidence: 99%
“…AE is reported to effectively reduce the fear of childbirth (Serçekuş & Başkale, 2016). A systematic review also reported that AE, psycho-education and counselling reduced the fear of birth and anxiety experienced during pregnancy (Aguilera-Martín et al, 2021). Additionally, it is reported that interventions to reduce the fear of birth in the antenatal period can potentially prevent psychological problems that may occur during the postpartum period (Challacombe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review of 18 studies, the authors concluded that some therapies might be effective, such as prenatal education, psychoeducation, and counseling. The result also showed that treatment such as cognitive behavioral therapy would benefit from more research (Aguliera-Martin et al 2021 ).…”
Section: Introductionmentioning
confidence: 96%